Venice GIS Portal: la punta dell'iceberg - Todaro, Rudj Maria (GEOmedia, 2010)
Venice GIS portal Single information system, the only methodology but an undetermined number of working groups. The basic principle, which underpins Insula, is flexibility, a philosophy which has enabled it to test the adoption of new processes of governance of assets, as a strategic resource of the Public.